Impaired central thyroid hormone sensitivity is associated with time in range in patients with type 2 diabetes mellitus in the euthyroid population - Xu Jiang; Yu Gong; Guojuan Wang; Ying Li (Diabetology & Metabolic Syndrome)
Abstract Objective To investigate the correlation between central thyroid hormone (TH) sensitivity and time in target glucose range (TIR) in patients with type 2 diabetes mellitus (T2DM). Methods 483 enrolled inpatients with T2DM were collected with the continuous glucose monitoring (CGM) data and clinical characteristics. Thyroid stimulating hormone index (TSHI), thyrotropin-thyroxine resistance index (TT4RI) and thyroid feedback quantile index (TFQI) were calculated. The correlations between TSHI, TT4RI, TFQI and TIR were statistically analyzed. Results The levels of FT4, TSHI, TT4RI and TFQI in TIR > 70% group were all higher compared with TIR ≤ 70% group (all P < 0.05). TSHI was positively correlated with TIR before the inflection point of 2.2 (β = 14.8, P < 0.001), and the correlation strengthened after there (β = 30.9, P < 0.001). TT4RI was positively correlated with TIR before the inflection point of 32 (β = 1.3, P < 0.001), and the correlation weakened after there (β = 0.7, P < 0.001). TFQI was not correlated with TIR before the inflection point of -0.6 (P = 0.302), but was positively correlated with TIR after there (β = 28.7, P < 0.001). For one-quartile increase in TSHI and TFQI, the odds of TIR-target (TIR > 70%) increased by 0.825 times and 1.3891 times respectively. Conclusion Decreased central TH sensitivity, namely increased TH resistance, is associated with elevated TIR, suggesting that central TH resistance maybe a protective factor for TIR.